2013
DOI: 10.1161/atvbaha.112.254961
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation by Heparanase Is Mediated by TLR-2 and TLR-4 and Associates With Plaque Progression

Abstract: Objective Factors and mechanisms that activate macrophages in atherosclerotic plaques are incompletely understood. We examined the capacity of heparanase to activate macrophages. Results/Methods Highly purified heparanase was added to mouse peritoneal macrophages (MPM) and macrophage-like J774 cells and the levels of TNFα, MMP-9, IL-1, and MCP-1 were evaluated by ELISA. Gene expression was determined by RT-PCR. Cells collected from Toll like receptor (TLR)-2 and -4 knockout mice (KO) were evaluated similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 68 publications
13
139
1
2
Order By: Relevance
“…It is conceivable that Sulfs or other HSPG modifying enzymes, such as matrix metalloproteases and heparanase, a heparan-degrading enzyme, might modulate the bioavailability of IFN-β in the macrophage microenvironment in a similar way. While we did no observe differences in heparanase expression in macrophages, increased heparanase expression has been linked to activation of innate immune cells, expression of inflammatory markers, such as CCL5, CCL2 and TNF-α, and plaque vulnerability (Blich et al, 2013; Osterholm et al, 2013). …”
Section: Discussioncontrasting
confidence: 82%
“…It is conceivable that Sulfs or other HSPG modifying enzymes, such as matrix metalloproteases and heparanase, a heparan-degrading enzyme, might modulate the bioavailability of IFN-β in the macrophage microenvironment in a similar way. While we did no observe differences in heparanase expression in macrophages, increased heparanase expression has been linked to activation of innate immune cells, expression of inflammatory markers, such as CCL5, CCL2 and TNF-α, and plaque vulnerability (Blich et al, 2013; Osterholm et al, 2013). …”
Section: Discussioncontrasting
confidence: 82%
“…We also found increased heparanase expression in severe atherosclerotic plaques and in arterial segments of the coronary vessels with low shear stress in a diabetic, hyperlipidemic porcine model of atherosclerosis (27). This finding has recently been corroborated in atherosclerotic plaques from human patients (55). Another study has also identified heparanase to be key in controlling the inflammatory response in sepsis through degradation of the glycocalyx (56).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 72%
“…Importantly, this effect was dependent on catalytic activity of the enzyme, and Lerner et al (48) proposed that heparanase relieves a HS-mediated inhibition of LPS-induced TLR4 signaling, supporting previous work by Brunn et al (49). In accord with these findings Blich et al reported loss of the pro-inflammatory activity of recombinant heparanase in peritoneal macrophages isolated from TLR2 and TLR4 knock-out mice (50). In a related context HS has also been considered an endogenous TLR4 agonist (51).…”
Section: Discussionmentioning
confidence: 76%